PENGARUH DISIPLIN, KOMPENSASI DAN PENDIDIKAN DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PERKEBUNAN WANNA JINGGA PADA PT. DUTA PALMA NUSANTARA DI BASERAH KABUPATEN KUANTAN SINGINGI - Ririn Suriantini; Machasin '; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of compensation, Discipline, Education and Training on Productivity and Factory Employees at PT. Duta Palma Nusantara In Baserah Kabupaten Kuantan Singingi. And to know which is the most dominant factor influential Against Employee Productivity Perkebunan Wanna Jingga Pada PT. Duta Palma Nusantara di Baserah Kabupaten Kuantan Singingi The population in this study were all employees of Perkebunan Wanna Jingga Pada PT. Duta Palma Nusantara, totaling 175 people. In the sampling, the author uses simple random sampling method, a total of 64 people. In this study, the data obtained will be processed by multiple linear regression model (multiple regression). Regression method can be used to show how the independent variables affect the dependent variable. From the research, the first hypothesis testing results show that the effect on Work Productivity discipline. The results of the two compensation effect hypothesis Against Employee Productivity. The results of testing the third hypothesis influential education and training Against Employee Productivity Perkebunan Wanna Jingga Pada PT. Duta Palma Nusantara di Baserah Kabupaten Kuantan Singingi. The most dominant and influential factors Against Employee Productivity Orange Factory and Plantation Want In Perkebunan Wanna Jingga Pada PT. Duta Palma Nusantara di Baserah Kabupaten Kuantan Singingi is compensated.Keywords: Compensation, Discipline, Education and Training and productivity